Framing the Social Responsibility Role of Islamic Financial Institutions within a Three-sector Economic Model - Barom, Mohd Nizam (2019)
Purpose: This paper examines and reflects the ongoing debate on the social responsibility role of Islamic financial institutions (IFIs) in the light of the literature in the area of third sector and three-sector economic model. Subsequently, it seeks to develop a framework that can be used to conceptualise the potential interaction between the different sectors in the economy in relation to social welfare issues and locate the social responsibility role of IFIs within this framework.